Survei Persepsi Siswa Terhadap Konsep Pendidikan Jasmani SMP Kelas VIII - Cahyono, Aprianto; Mu’arifin, Mu’arifin (Universitas Negeri Malang, 2020)
Abstract: The objectives of this study were: (1) to examine the level of perceptions of male and female students towards the concept of junior high school physical education in Kediri Regency, (2) to examine differences in the perceptions of male and female students towards the concept of junior high school physical education in Kediri Regency. This type of research is descriptive quantitative using a survey method. The result is that the percentage of the understanding of physical education is 80% of the results of the percentage of physical education goals, 73% of the percentage of physical activity, of 77% and of the percentage of the concept of physical education of 76%. After knowing the level of understanding, the researchers distinguished male and female students 'perceptions of the concept of physical education, obtained a significant value of 0.589 with a significance level of more than 0.05, meaning it was not accepted, thus the results of male and female students' perceptions of the concept of physical education did not experience a difference. . The conclusion of this study is the perception of students of class VIII SMP in Kediri Regency is good.Â Abstrak:Tujuan dari penelitian ini adalah: (1) untuk mengkaji tingkat persepsi siswa laki-laki dan perempuan terhadap konsep pendidikan jasmani SMP di Kabupaten Kediri, (2) untuk mengkaji perbedaan persepsi siswa laki-laki dan perempuan terhadap konsep pendidikan jasmani SMP di Kabupaten Kediri. Jenis penelitian ini deskriptif kuantitatif dengan menggunakan metode survei. Hasilnya yaitu dari persentase pengertian pendidikan jasmani 80% hasil dari persentase tujuan pendidikan jasmani 73% hasil dari persentase aktivitas jasmani 77% dan hasil dari persentase konsep pendidikan jasmani 76%. Setelah mengetahui tingkat pemahaman peneliti membedakan persepsi siswa laki-laki dan perempuan terhadap konsep pendidikan jasmani di peroleh nilai signifikan 0,589 dengan taraf signifikansi lebih dari 0,05 artinya tidak diterima dengan demikian hasil persepsi siswa laki-laki dan perempuan terhadap konsep pendidikan jasmani tidak menglami perbedaan. Kesimpulan dari penelitian ini adalah persepsi siswa kelas VIII SMP di Kabupaten Kediri adalah baik.